Chinese in Aotearoa and their attitudes towards and experiences of talking therapies/mental health in Aotearoa : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Clinical Psychology at Massey University, Albany, New Zealand - Qiu, Luyu (Massey University, 2025)
Extensive research has examined the effectiveness of various “talking therapies” across populations and mental health disorders. Literature suggests that current “talking therapies”, which are mainly based on Western values and theories, could be culturally adapted to improve effectiveness and overall experience for individuals from other cultural backgrounds. The Chinese population in Aotearoa has been steadily growing over the past decades, and are a diverse and heterogeneous population. Despite being viewed as the “model minority”, research suggests that there is also a need to address their mental health issues. However, despite the knowledge that culturally adapted talking therapies could be more effective, this area has often been neglected in research where there is limited information regarding the Chinese in Aotearoa population and their experiences with talking therapies and their attitudes towards mental health. This study aims to bridge this gap in the literature. This study utilized a qualitative methodology where 14 participants who identified as Chinese in Aotearoa with prior experience of “talking therapies” engaged in one-on-one semi-structured interviews. Thematic analysis revealed several themes categorised into pre-therapeutic experiences and during/post-therapeutic experiences. Pre-therapeutic experiences revealed the unique challenges and barriers that this population face before engaging in mental health services and the highly vulnerable state they are in when presenting at services. Notably, recommendations from trusted individuals could mitigate the barriers to accessing services. The during/post-therapeutic experiences revealed the importance of using psychoeducation, having a safe non-judgmental therapeutic space, culturally responsive and sensitive practice, and key factors leading to a positive therapeutic alliance. Markedly, there was an observed reluctance to involve family members as well as use of medication. It also highlights the importance of the therapeutic experience as a positive experience could contribute to de-stigmatization of mental health for this population. The findings underscore a need to address the barriers of accessing mental health support and implementing culturally responsive evidence-based practice for this population. This study aims to serve as a foundation for future research in the development of best-practice approaches and to evoke the continual movement in exploring and improving talking therapies in Aotearoa with this growing Chinese in Aotearoa population.
Keywords: Chinese in Aotearoa; talking therapy; barriers; cultural adaptations; mental health; client experiences; qualitative research; 52 Psychology::5203 Clinical and health psychology::520302 Clinical psychology; 42 Health sciences::4203 Health services and systems::420313 Mental health services